2016
DOI: 10.1186/s12877-016-0373-4
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and cost-effectiveness of an in-home respite care program in supporting informal caregivers of people with dementia: design of a comparative study

Abstract: BackgroundFrequent hospitalization and permanent nursing home placement not only affect the well-being of persons with dementia, but also place great financial strain on society. Therefore, it is important to create effective strategies to support informal caregivers so that they can continue to perform their demanding role. Preliminary qualitative evidence suggests that community-based respite services can actually be important for caregivers, and that the level of evidence should be further established in te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(36 citation statements)
references
References 41 publications
0
35
0
1
Order By: Relevance
“…These results highlight the importance of effective caregiver support to decrease their burden [16, 36]. Another modifiable independent associated factor was the impact of behavioral disturbances on the CG.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…These results highlight the importance of effective caregiver support to decrease their burden [16, 36]. Another modifiable independent associated factor was the impact of behavioral disturbances on the CG.…”
Section: Discussionmentioning
confidence: 82%
“…The baseline data from an ongoing prospective study titled “Effectiveness and cost-effectiveness of an in-home respite care program in supporting informal CG of people with dementia” were used, see Vandepitte et al [16]. Ethical approval (B670201526906) for this trial was obtained, and the trial is registered on clinicaltrials.gov, ID: NCT02630446.…”
Section: Design and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…21 Ethical approval (B670201526906) was obtained, and the trial was registered on clinicaltrials.gov, ID: NCT02630446. 21 Ethical approval (B670201526906) was obtained, and the trial was registered on clinicaltrials.gov, ID: NCT02630446.…”
Section: Methodsmentioning
confidence: 99%
“…Numerous studies have employed interventions to reduce caregiver burden and depression [7]. The majority of caregiver instruments employed in these studies rely on self-reported scales assessing subjective aspects of caregiving to determine the level of caregiver burden experienced [8, 9].…”
Section: Introductionmentioning
confidence: 99%